The divine Christ : Paul, the Lord Jesus, and the scriptures of Israel - Capes, David B. (Grand Rapids, MI. : Baker Academic., 2018)
For the past century, scholars have debated when and how a divine Christology emerged. This book considers the earliest evidence we have, the letters of Paul. David Capes, a veteran teacher and highly regarded scholar, examines Paul's letters to show how the apostle constructed his unique portrait of Jesus as divine through a rereading of Israel's Scriptures.
"Lord" and "lord" in the Bible -- Kyrios/Lord as a christological title -- Jesus as Kyrios in Paul's letters -- YHWH texts with God as referent -- YHWH texts with Christ as referent -- Pauline exegesis and a high Christology -- Conclusion.
Includes bibliographical references (pages 189-193) and indexes.
Keywords: Jesus Christ -- Divinity -- Biblical teaching; Jesus Christ -- Name -- Biblical teaching; Bible. -- Criticism, interpretation, etc; Bible. -- Relation to the Old Testament